Developing of multiple motor drive module system with real-time data-acquisition channels - Irawan, Addie (2008)
Currently a lot of manufacturing and plantation machines in factory uses electrical-based actuator or motor as a core driver to execute the required process, instead of using pneumatic-based and hydraulic-based actuator. Alternating current (AC) motor is commonly used in the factory because of the low cost and could also provide high power drives. However, direct current (DC) motor and DC stepper motor still playing a main role for small scale and low power applications. Most of the recent controller module separately and specifically weather for DC motor or AC motor only. On the other hand computerbased control is very demanding seems the information technology growth rapidly with the computer technology. Therefore, the project is initiated to develop a multiple motor drive module system with real-time data acquisition channels (MMDS-RTD). Data acquisition channels are common tools for industrial automation applications because actual performance data is very important for precision control. MMDS-RTD was designed with capability of control the DC motor (maximum: 600VDC, 3A), Stepper Motor (maximum: 24VDC, 3A) and single-phase AC induction motor (maximum: 50Hz, 240V AC, 720W). 5 channels of Analog-to-Digital (AID) with range between 0 to 5VDC voltage input each with 3 channels adjustable for Digital-to-Digital (DD) signal. This module is also prepared with programmable with the law that has been setup. Thus all high level program language can be used with MMDS-RTD module via serial communication (RS232) for control and universal serial bus (USB) for data acquisitions. However this project also designed and developed a specific graphical user interface (GUl) for MMDS-RTD for evaluation and verification purposes. The MMDS-RTD is designed with multi-protocol communication interfaces include RS232 serial protocol, USB protocol and Bluetooth. On internal system layer, MMDS-RTD is designed with multiprocessor technology and mixed-bridge inverter. Fast single way inter-processor switching has been designed with label/tag switching approaches. This type of switching has capable to aggregate data addressing and dynamic address. swap-ping. Besides Single Spindle 2-Axis Filament Winding (SSFWM) machine has been fabrication for MMDS-RTD validation on industrial machine application. As a result MMDS-RTD Alpha version has successfully applied for this machine for with particular graphical user interface (GUI) system